Penerapan Jaminan Fidusia dalam Leasing Kendaraan Bermotor : Analisis Terhadap Penyalagunaan dan Perlindungan Konsumen - Mahmudah, Siti; Mutmainah, Siti; Wulandari, Tika; Huda, A. Thoriqil (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Fiduciary guarantees serve as a key legal mechanism in motor vehicle leasing, offering security for both creditors and consumers. Despite clear statutory regulations, enforcement remains inconsistent, leading to frequent consumer rights violations—particularly through unilateral vehicle repossessions without court approval. This study applies a normative legal approach to examine the misuse of fiduciary guarantees in Indonesia and evaluates the effectiveness of consumer legal protection. Findings indicate a persistent gap between regulatory frameworks and implementation, underscoring the need for stricter oversight and enforcement to safeguard consumer interests in leasing transactions.